COGNITIVE AND METHODOLOGICAL FOUNDATIONS OF SIMULTANEOUS INTERPRETATION IN MULTILINGUAL CONTEXTS - Utapova Oysapar Urazmatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores the concept, methodology, and practical applications of simultaneous interpretation (SI) in multilingual communication. It analyzes the development of SI as a profession, its theoretical underpinnings, and the cognitive skills required of interpreters. The paper also includes a review of relevant literature, research methods used to study SI performance, and a discussion of findings from observational and experimental data. The conclusion outlines the challenges and recommendations for improving training and performance in this field.